Bacterial Etiology of Bronchoalveolar Lavage Fluid in Tertiary Care Patients and Antibiogram of the Isolates - Adhikari, Sanjib; Regmi, Ramesh Sharma; Pandey, Siddanta; Paudel, Parash; Neupane, Nischal; Chalise, Shyam; Dubey, Ashok; Kafle, Sarad Chandra; Rijal, Komal Raj (Journal of Institute of Science and Technology, 2021)
Bronchoalveolar Lavage (BAL) is a medical technique by which cells and fluids from bronchioles and lung alveoli are withdrawn for diagnosis of disease or evaluation of treatment. Patients with various pulmonary infections follow the procedure of BAL for the disease diagnosis as it has high sensitivity and reliability in diagnosis. To examine the bacterial etiology of BAL fluids among tertiary care patients with pulmonary infections, a cross-sectional study was conducted over a period of three months from August to November 2018. A total of 149 BAL fluid samples were examined and the bacterial agents were isolated and identified by conventional microbiological methods. Out of the 149 samples, 142 samples were culture positive. Among 6 different isolates (4 Gram-negative and 2 Gram-positive), Pseudomonas aeruginosa (45 %) was predominant followed by Klebsiella pneumoniae (25.3 %). A higher infection rate was seen among males (62.4 %) and in the age group 60-70 years (30.0 %). In addition, 25.4 % (36/149) samples were positive in Acid Fast staining. Bacterial recovery from the BAL fluid was significantly associated with the gender and age of the patients (p<0.05). Gentamycin was the least resisted (1.5 %) by Gram-negative isolates followed by Polymyxin-B (3 %). For Gram-positive isolates, Ofloxacin was the most effective drug resisted by none of the isolates followed by Gentamycin. Among the 157 isolates, 125 (79.6 %) were MDR and 35.0 % of Enterobacteriaceae were ESBL producers. Detection of bacterial agents from BAL fluid can be a basis for successful antimicrobial therapy for patients with pulmonary infections.